Recruitment and Selection System of Human Resources at the Bina Iman Taqwa Foundation - Widi Setianah; Arief Yulianto; Suwito Eko Pramono; Gesine Schwan (Edukasi, 2023)
In the world of education, every organization or company needs resources to achieve its goals. Human resources are a basic need in an agency, so it needs to be carefully planned to recruit them. This study aims to determine and understand the process of recruitment and selection of human resources, the recruitment and selection process is appropriate , the feasibility of recruitment and selection of human resources at the Bina Insan Taqwa Foundation, Semarang. This study uses a qualitative research method with a case study approach. Data collection techniques namely Participatory Observation, Structured Interviews , and Documentation Studies . Data validity techniques include extension techniques, persistence in in-depth observation, triangulation of 3 types, and holding member checks. Data analysis techniques using data collection, data reduction, data presentation, and withdrawal/verification conclusions. Based on the results of this study, the selection process certainly has its own mechanism until finally the applicant or prospective employee is appointed as a new employee. However, there are stages or considerations such as medical tests not yet included in the selection stage. In general, these stages have a different order but the meaning and content of the selection stages are the same. Referring to Simamora's theory, there is a selection stage for the Bina Insan Taqwa foundation that has not been carried out, namely a physical examination or medical test. The feasibility of recruiting and selecting human resources at the Bina Insan Taqwa Foundation Semarang, can be seen in two aspects: 1) dissemination of information, and 2) the implementation of recruitment and selection is less than optimal. The results of this study can be used to add insight regarding Human Resources Recruitment And Selection System.